Histone Deacetylase Inhibitors in Pediatric Brain Cancers: Biological Activities and Therapeutic Potential - Perla, Alexandre; Fratini, Lívia; Cardoso, Paula S.; Nör, Carolina; Brunetto, André T.; Brunetto, Algemir L.; de Farias, Caroline Brunetto; Jaeger, Mariane; Roesler, Rafael (Frontiers in Cell and Developmental Biology, 2020)
Brain cancers are the leading cause of cancer-related deaths in children. Biological changes in these tumors likely include epigenetic deregulation during embryonal development of the nervous system. Histone acetylation is one of the most widely investigated epigenetic processes, and histone deacetylase inhibitors (HDACis) are increasingly important candidate treatments in many cancer types. Here, we review advances in our understanding of how HDACis display antitumor effects in experimental models of specific pediatric brain tumor types, i.e., medulloblastoma (MB), ependymoma (EPN), pediatric high-grade gliomas (HGGs), and rhabdoid and atypical teratoid/rhabdoid tumors (ATRTs). We also discuss clinical perspectives for the use of HDACis in the treatment of pediatric brain tumors.